Out-furnace metamorphic silicon-manganese alloy steel and heat treatment method thereof

Through the heat treatment method of metamorphic silicon-manganese alloy steel outside the furnace, a specific structure is formed, which solves the problem of insufficient hardness and wear resistance, improves the hardness and wear resistance of silicon-manganese alloy steel, and is suitable for power tools and strengthens the strength of Safety and lifespan in wind and sand environments.

CN119177405APending Publication Date: 2024-12-24STEJT GRID ELEKTRIK PAUER INZHINIRING RISERCH INSTITYUT KO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411610881.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The existing silicon-manganese alloy steel has low hardness and poor wear resistance, especially when used in strong wind and sand environments, which affects the safety and service life of power tools.

Method used

The heat treatment method of out-of-furnace metamorphic silicon-manganese alloy steel, including smelting, austenitization treatment, quenching and distribution treatment of specific chemical components, forming slat martensite, dispersed carbides and stable residual austenite structure , improve hardness and wear resistance.

Benefits of technology

The hardness and wear resistance of silicon-manganese alloy steel are significantly improved, and the Rockwell hardness is increased by 15HRC, which is significantly improved in wear resistance and impact toughness. It is suitable for power connection metals and overcome the wear risks caused by strong wind and sand.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of metal wear-resistant materials, and discloses external metamorphic silicon-manganese alloy steel and a heat treatment method thereof, the alloy steel comprises the following components in percentage by weight: 0.5 to 0.55 weight percent of C, 1.97 to 2.04 weight percent of Mn, 1.5 to 1.6 weight percent of Si, 0.98 to 1.02 weight percent of Cr, 0.39 to 0.41 weight percent of Mo, 0.004 to 0.007 weight percent of B, 0.08 to 0.12 weight percent of Mg, 0.35 weight percent of rare earth magnesium alloy, 0.04 to 0.07 weight percent of Nb, 0.13 to 0.15 weight percent of Ce, 0.03 to 0.05 weight percent of V and the balance of Fe. According to the invention, a sample obtained by smelting and casting is subjected to heat treatment-quenching-partitioning treatment, so that the material has excellent hardness, wear resistance and obdurability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alloy steel processing, and particularly relates to an out-of-furnace modified silicon-manganese alloy steel and a heat treatment method thereof. Background Art

[0002] As the transmission lines cover a large area, the climate and geological conditions in the area are complex, and the operating natural environment is harsh. Strong winds can easily carry sand and dust, causing premature wear and failure of power connection hardware, which not only causes huge property losses, but also poses hidden dangers to the safe and stable operation of transmission lines. Ordinary hardware materials have low hardness and poor wear resistance, which seriously affects the safe use of hardware.

[0003] In order to improve the performance of power fittings, Chinese invention patent CN117038142A also discloses a tin-plated aluminum alloy power fitting, wherein the tin-plated aluminum alloy includes, by mass percentage, 1% to 40% Sn, 1% to 30% Ni, 0.003% to 5% Fe, 0.003% to 5% Cu, 0.001% to 3% Mg and 0.01% to 8% Zn, with the remainder being Al and impurities; the surface of the tin-plated aluminum alloy is provided with a tin-plated layer; the thickness of the tin-plated layer is 1 to 500 μm. The present invention greatly improves the hardness, wear resistance and toughness of the existing aluminum alloy material by tin-plating the surface of the aluminum alloy conductor material, and effectively optimizes the various performance indicators of the aluminum alloy as a power fitting material. The electrical fittings made of tin-plated aluminum alloy conductor material provided by this patent can be used not only for power cable terminals, but also for various types of terminals such as automotive wiring harnesses, photovoltaic dedicated lines, and electrical equipment lines. It greatly expands the application range of terminals made of aluminum alloy and can be used to replace nickel-plated or tin-plated copper terminals.

[0004] Chinese invention patent CN110760783A also discloses a method for improving the wear resistance of aluminum alloy electric hardware. The prepared ball-milled powder is quickly melted by plasma spraying technology to further form atomized molecules, which are sprayed onto the pretreated hardware surface and rapidly condensed to obtain a wear-resistant coating, which acts as an inert wear-resistant and anti-corrosion barrier. The coating has a strong bonding force with the surface of the aluminum alloy hardware, a dense film layer, and high hardness. It can withstand the test of high-intensity external force impact, so that the surface performance of the hardware is comprehensively improved, and the safety and service life of the electric hardware are improved. The present invention can significantly improve the wear resistance of aluminum alloy electric hardware, solve the problem that the existing aluminum alloy electric hardware is not wear-resistant, improve the surface strength and toughness, stabilize the chemical and mechanical properties, expand its application occasions, and significantly improve the economic and safety benefits.

[0005] However, the hardware manufacturing technology disclosed in the above patents generally has the disadvantages of low hardware hardness and poor wear resistance when used in strong wind and sand environment. Summary of the invention

[0006] In order to solve the problem of low hardness and poor wear resistance of silicon-manganese alloy steel, the purpose of the present invention is to provide a furnace-modified silicon-manganese alloy steel and a heat treatment method thereof, wherein the furnace-modified silicon-manganese alloy steel treated by the method has good hardness, wear resistance and impact toughness.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A furnace-modified silicon-manganese alloy steel comprises, by weight percentage, 0.5-0.55 wt.% C, 1.97-2.04 wt.% Mn, 1.5-1.6 wt.% Si, 0.98-1.02 wt.% Cr, 0.39-0.41 wt.% Mo, 0.004-0.007 wt.% B, 0.08-0.12 wt.% Mg, 0.35 wt.% rare earth magnesium alloy, 0.04-0.07 wt.% Nb, 0.13-0.15 wt.% Ce, 0.03-0.05 wt.% V, and the remainder is Fe and inevitable trace impurities.

[0008] A further improvement of the present invention is that the rare earth magnesium alloy comprises, by mass percentage, 11.07-12.22 wt.% Mg, 2.01-2.56 wt.% rare earth elements, 40.38-42.25 wt.% Si, 2.05-2.60 wt.% Ca, and the remainder is Fe.

[0009] A heat treatment method for out-of-furnace modified silicon-manganese alloy steel comprises the following steps: According to the chemical composition of the modified silicon-manganese alloy steel outside the furnace, scrap steel, ferrochrome, ferrosilicon, ferroboron and ferromanganese are melted, and a deoxidizer is added after the molten steel is heated to a first temperature; The molten steel is transferred to a ladle, the bottom of which contains rare earth magnesium alloy, ferroniobium and ferrovanadium modifiers; After cooling the molten steel to a second temperature, casting is performed to obtain a sample; The samples were austenitized, quenched and then partitioned.

[0010] A further improvement of the present invention is that the first temperature is 1640-1660°C.

[0011] A further improvement of the present invention is that the amount of the deoxidizer added is 0.04-0.06% of the mass of the silicon-manganese alloy steel modified outside the furnace.

[0012] A further improvement of the present invention is that the second temperature is 1550-1570°C.

[0013] A further improvement of the present invention is that the temperature of the austenitizing treatment is 850-870° C. and the holding time is 30-35 minutes.

[0014] A further improvement of the present invention is that the quenching temperature is 170-190° C. and the holding time is 120-140 seconds.

[0015] A further improvement of the present invention is that the temperature of the distribution treatment is 340-360° C. and the holding time is 60-70 seconds.

[0016] A further improvement of the present invention is that the microstructure of the heat-treated out-of-furnace modified silicon-manganese alloy steel includes: lath martensite with a width range of 200-300 nm, dispersed carbides and residual austenite with a volume percentage of 3-5%.

[0017] The further improvement of the present invention is that the hardness of the heat-treated out-of-furnace modified silicon-manganese alloy steel is above 58HRC and the wear resistance is 10-11 min / mg. Compared with the prior art, the present invention has the following beneficial effects: In the present invention, after heat treatment-quenching-partitioning heat treatment, the microstructure of the alloy steel is mainly composed of lath martensite, residual austenite and dispersed carbides. After metamorphism, the width of the martensite lath is significantly refined, and the average width is refined from 420 nm to about 290 nm. The wear resistance and toughness of the alloy steel are improved by precipitation strengthening of carbides, fine grain strengthening of metamorphism and increasing the content of residual austenite. The volume fraction of austenite in the silicon-manganese alloy steel of the present invention is about 9%, and the Rockwell hardness of the silicon-manganese alloy steel after metamorphism is greater than 58 HRC, which is 15HRC higher than that of the cast sample. In addition, the metamorphosed silicon-manganese alloy steel has good wear resistance and impact toughness, and the room temperature impact toughness (α KU ) increased by 20%, exceeding 50J / cm 2 , 196 N low stress wear performance increased by 37%, 392 N high stress wear performance increased by 12%.

[0018] Furthermore, based on silicon-manganese steel, a new type of silicon-manganese low alloy cast steel is provided through component optimization and heat treatment process improvement, and the strength, toughness and wear resistance of silicon-manganese alloy steel are improved. Its main characteristics are that elements such as Cr and B are added to the silicon-manganese alloy steel, combined with rare earth magnesium alloy and Nb, V composite metamorphism treatment, and its wear resistance is improved through the effect of fine grain strengthening. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 It is a specific quenching-partitioning heat treatment process flow chart; Figure 1 In the figure, AT, QT and PT represent austenitizing temperature, quenching temperature and partitioning temperature respectively. DETAILED DESCRIPTION

[0019] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.

[0020] The invention discloses a modified silicon-manganese alloy steel, the chemical composition of which comprises, by weight percentage, 0.5-0.55 wt.% C, 1.97-2.04 wt.% Mn, 1.5-1.6 wt.% Si, 0.98-1.02 wt.% Cr, 0.39-0.41 wt.% Mo, 0.004-0.007 wt.% B, 0.08-0.12 wt.% Mg, 0.35 wt.% RE-Mg (rare earth magnesium alloy), 0.04-0.07 wt.% Nb, 0.13-0.15 wt.% Ce, 0.03-0.05 wt.% V, and the rest are Fe and inevitable trace impurities, and the rare earth elements RE include but are not limited to La, Ce, Y and Er.

[0021] See also Figure 1 The heat treatment method of modified silicon-manganese alloy steel of the present invention comprises the following steps: 1) According to the chemical composition of the modified silicon-manganese alloy steel, the required scrap steel, ferrochrome, ferrosilicon, ferroboron and ferromanganese are placed in an induction furnace for smelting. After the composition is adjusted to be qualified before the furnace, the molten steel is heated to 1640-1660°C and then 0.04-0.06wt.% of pure Al is added as a deoxidizer, which accounts for 0.04-0.06wt.% of the weight of the modified silicon-manganese alloy steel.

[0022] 2) Take the molten steel out of the furnace and pour it into a ladle, at the bottom of which rare earth magnesium alloy, ferroniobium and ferrovanadium modifiers are placed in advance. The composition of the rare earth magnesium alloy, by mass percentage, includes: 11.07-12.22 wt.% Mg; 2.01-2.56 wt.% RE; 40.38-42.25 wt.% Si; 2.05-2.60 wt.% Ca; the rest is Fe.

[0023] 3) When the temperature of molten steel drops to 1550-1570°C, it is directly cast into a resin sand casting mold, air-cooled to room temperature after being taken out of the furnace, and cast into a mold with good shrinkage compensation performance. Y Type test block, Y The test block is cut into specimens with a thickness of 10-20 mm.

[0024] 4) The sample is austenitized in a resistance furnace at 850-870°C for 30-35 minutes, then quenched in a salt bath to 170-190°C for 120-140 seconds, then partitioned in a salt bath solution at 340-360°C for 60-70 seconds, and finally air-cooled to room temperature.

[0025] The microstructure of the modified silicon-manganese alloy steel after heat treatment is: lath martensite with a width range of 200~300nm, dispersed fine carbides and stable residual austenite with a volume white fraction of 3-5%. The hardness is above 58HRC and the wear resistance is 10~11 min / mg.

[0026] The following are specific embodiments.

[0027] Example 1 1) Put the required scrap steel, ferrochrome, ferrosilicon, ferroboron and ferromanganese into a 100 kg induction furnace for smelting. After adjusting the composition in front of the furnace to meet the requirements, heat the molten steel to 1650°C and add 0.05wt.% pure Al as a deoxidizer.

[0028] 2) Take the molten steel out of the furnace and pour it into a ladle, at the bottom of which rare earth magnesium alloy, ferroniobium and ferrovanadium modifiers are placed in advance. The composition of the rare earth magnesium alloy includes, by mass percentage, 11.07-12.22 wt.% Mg, 2.01-2.56 wt.% Ce, 40.38-42.25 wt.% Si, 2.05-2.60 wt.% Ca, and the rest is Fe. The final chemical composition of the molten steel includes, by mass percentage, 0.5~0.55 wt.%C, 1.97~2.04 wt.%Mn, 1.5~1.6 wt.%Si, 0.98~1.02 wt.%Cr, 0.39~0.41wt.%Mo, 0.004~0.007 wt.%B, 0.08~0.12wt.% Mg, 0.04~0.07 wt.%Nb, 0.13~0.15wt.%Ce, 0.03~0.05 wt.%V, and the rest is Fe and inevitable trace impurities.

[0029] 3) When the temperature of the molten steel drops to 1560°C, it is directly cast into a resin sand mold. After being taken out of the furnace, it is air-cooled to room temperature and cast into a Y-shaped test block with good shrinkage compensation performance. The Y-shaped test block is wire-cut into a sample with a thickness of 10 mm.

[0030] 4) The sample was austenitized in a resistance furnace at 860°C and kept warm for 30 min, then quenched in a salt bath to 180°C and kept warm for 120 s, then partitioned in a salt bath solution at 350°C for 1 min, and finally air-cooled to room temperature to obtain silicon-manganese alloy steel. Its mechanical properties and wear resistance are shown in Table 1.

[0031] Example 2 1) Put the required scrap steel, ferrochrome, ferrosilicon, ferroboron and ferromanganese into a 200 kg induction furnace for smelting. After adjusting the composition in front of the furnace to meet the requirements, heat the molten steel to 1650°C and add 0.05% pure Al as a deoxidizer.

[0032] 2) Take the molten steel out of the furnace and pour it into a ladle, at the bottom of which rare earth magnesium alloy, ferroniobium and ferrovanadium modifiers are placed in advance. The composition of the rare earth magnesium alloy is: 11.07-12.22 wt.% Mg, 2.01-2.56 wt.% La, 40.38-42.25 wt.% Si, 2.05-2.60 wt.% Ca, and the rest is Fe. The final chemical composition of the molten steel, calculated by mass percentage, includes: 0.5~0.55wt.%C, 1.97~2.04 wt.%Mn, 1.5~1.6 wt.%Si, 0.98~1.02 wt.%Cr, 0.39~0.41 wt.%Mo, 0.004~0.007 wt.%B, 0.08~0.12wt.% Mg, 0.04~0.07 wt.%Nb, 0.13~0.15wt.%Ce, 0.03~0.05 wt.%V, and the rest is Fe and inevitable trace impurities.

[0033] 3) When the temperature of the molten steel drops to 1560°C, it is directly cast into a resin sand mold. After being taken out of the furnace, it is air-cooled to room temperature and cast into a Y-shaped test block with good shrinkage compensation performance. The Y-shaped test block is wire-cut into a sample with a thickness of 20 mm.

[0034] 4) The sample was austenitized in a resistance furnace at 860°C, kept warm for 30 min, then quenched in a salt bath to 180°C, kept warm for 120 s, and then partitioned in a salt bath solution at 350°C for 1 min. Finally, it was air-cooled to room temperature to obtain a modified silicon-manganese alloy steel. Its mechanical properties and wear resistance are shown in Table 1.

[0035] Example 3 1) Put the required scrap steel, ferrochrome, ferrosilicon, ferroboron and ferromanganese into a 150 kg induction furnace for smelting. After adjusting the composition in front of the furnace to meet the requirements, heat the molten steel to 1650°C and add 0.05% pure Al as a deoxidizer.

[0036] 2) Take the molten steel out of the furnace and pour it into a ladle, at the bottom of which rare earth magnesium alloy, ferroniobium and ferrovanadium modifiers are placed in advance. The composition of the rare earth magnesium alloy is: 11.07-12.22 wt.% Mg; 2.01-2.56 wt.% Y; 40.38-42.25 wt.% Si; 2.05-2.60 wt.% Ca; the rest is Fe. The final chemical composition of the molten steel, calculated by mass percentage, includes: 0.5~0.55 wt.%C, 1.97~2.04 wt.%Mn, 1.5~1.6 wt.%Si, 0.98~1.02 wt.%Cr, 0.39~0.41 wt.%Mo, 0.004~0.007 wt.%B, 0.08~0.12wt.% Mg, 0.04~0.07 wt.%Nb, 0.13~0.15wt.%Ce, 0.03~0.05 wt.%V, and the rest is Fe and unavoidable trace impurities.

[0037] 3) When the temperature of the molten steel drops to 1560°C, it is directly cast into a resin sand mold. After being taken out of the furnace, it is air-cooled to room temperature and cast into a Y-shaped test block with good shrinkage compensation performance. The Y-shaped test block is wire-cut into a sample with a thickness of 15 mm.

[0038] 4) The sample was austenitized in a resistance furnace at 860°C, kept warm for 30 min, then quenched in a salt bath to 180°C, kept warm for 120 s, and then partitioned in a salt bath solution at 350°C for 1 min. Finally, it was air-cooled to room temperature to obtain a modified silicon-manganese alloy steel. Its mechanical properties and wear resistance are shown in Table 1.

[0039] Example 4 1) Put the required scrap steel, ferrochrome, ferrosilicon, ferroboron and ferromanganese into a 100 kg induction furnace for smelting. After adjusting the composition in front of the furnace to meet the requirements, heat the molten steel to 1650°C and add 0.05% pure Al as a deoxidizer.

[0040] 2) Take the molten steel out of the furnace and pour it into a ladle, at the bottom of which rare earth magnesium alloy, ferroniobium and ferrovanadium modifiers are placed in advance. The composition of the rare earth magnesium alloy is: 11.07-12.22 wt.% Mg, 2.01-2.56 wt.% Er, 40.38-42.25 wt.% Si, 2.05-2.60 wt.% Ca, and the rest is Fe. The final chemical composition of the molten steel, calculated by mass percentage, includes: 0.5~0.55wt.%C, 1.97~2.04 wt.%Mn, 1.5~1.6 wt.%Si, 0.98~1.02 wt.%Cr, 0.39~0.41 wt.%Mo, 0.004~0.007 wt.%B, 0.08~0.12wt.% Mg, 0.04~0.07 wt.%Nb, 0.13~0.15wt.%Ce, 0.03~0.05 wt.%V, and the rest is Fe and inevitable trace impurities.

[0041] 3) When the temperature of the molten steel drops to 1560°C, it is directly cast into a resin sand mold. After being taken out of the furnace, it is air-cooled to room temperature and cast into a Y-shaped test block with good shrinkage compensation performance. The Y-shaped test block is wire-cut into a sample with a thickness of 18 mm.

[0042] 4) The sample was austenitized in a resistance furnace at 860°C, kept warm for 30 min, then quenched in a salt bath to 180°C, kept warm for 120 s, and then partitioned in a salt bath solution at 350°C for 1 min. Finally, it was air-cooled to room temperature to obtain a modified silicon-manganese alloy steel. Its mechanical properties and wear resistance are shown in Table 1.

[0043] Example 5 1) Put the required scrap steel, ferrochrome, ferrosilicon, ferroboron and ferromanganese into a 100 kg induction furnace for smelting. After adjusting the composition in front of the furnace to meet the requirements, heat the molten steel to 1640°C and add 0.04% pure iron as a deoxidizer.

[0044] 2) Take the molten steel out of the furnace and pour it into a ladle. Rare earth magnesium alloy, ferroniobium and ferrovanadium modifiers are placed at the bottom of the ladle. The composition of the rare earth magnesium alloy includes 11.07 wt.% Mg, 2.01 wt.% Ce, 40.38 wt.% Si, 2.05 wt.% Ca, and the rest is Fe. The final chemical composition of the molten steel includes 0.5 wt.% C, 1.97 wt.% Mn, 1.6 wt.% Si, 1.02 wt.% Cr, 0.39 wt.% Mo, 0.004 wt.% B, 0.08 wt.% Mg, 0.07 wt.% Nb, 0.15 wt.% Ce, 0.05 wt.% V, and the rest is Fe and unavoidable trace impurities.

[0045] 3) When the temperature of the molten steel drops to 1570°C, it is directly cast into a resin sand mold. After being taken out of the furnace, it is air-cooled to room temperature and cast into a Y-shaped test block with good shrinkage compensation performance. The Y-shaped test block is wire-cut into a sample with a thickness of 10 mm.

[0046] 4) The sample was austenitized in a resistance furnace at 850 °C for 35 min, then quenched in a salt bath to 190 °C for 120 s, then partitioned in a salt bath at 340 °C for 70 s, and finally air-cooled to room temperature.

[0047] Example 6 1) Put the required scrap steel, ferrochrome, ferrosilicon, ferroboron and ferromanganese into a 100 kg induction furnace for smelting. After adjusting the composition in front of the furnace to meet the requirements, heat the molten steel to 1660°C and add 0.06% pure magnesium as a deoxidizer.

[0048] 2) Take the molten steel out of the furnace and pour it into a ladle. Rare earth magnesium alloy, ferroniobium and ferrovanadium modifiers are placed at the bottom of the ladle. The composition of the rare earth magnesium alloy includes 12.22 wt.% Mg, 2.56 wt.% Ce, 42.25 wt.% Si, 2.60 wt.% Ca, and the rest is Fe. The final chemical composition of the molten steel includes 0.55 wt.% C, 2.04 wt.% Mn, 1.5 wt.% Si, 0.98 wt.% Cr, 0.41 wt.% Mo, 0.007 wt.% B, 0.12 wt.% Mg, 0.04 wt.% Nb, 0.13 wt.% Ce, 0.03 wt.% V, and the rest is Fe and unavoidable trace impurities.

[0049] 3) When the temperature of the molten steel drops to 1550°C, it is directly cast into a resin sand mold. After being taken out of the furnace, it is air-cooled to room temperature and cast into a Y-shaped test block with good shrinkage compensation performance. The Y-shaped test block is wire-cut into a sample with a thickness of 10 mm.

[0050] 4) The sample was austenitized in a resistance furnace at 870 °C for 30 min, then salt-bath quenched to 170 °C for 140 s, then partitioned in a salt bath at 360 °C for 1 min, and finally air-cooled to room temperature.

[0051] The preparation process of the modified silicon-manganese alloy steel of the present invention is relatively simple. The hardness of the sample is tested by using an MHR-150 electric Rockwell hardness tester, and the applied load is 150 kg; the wear resistance test of the sample is carried out by using an MM-200 ring block wear tester, the test load is 196 N, the time is 120 min, the speed of the tester is 200 rpm, and the wear sample is weighed once every 30 min; the room temperature impact toughness test is carried out by using a JB230 impact tester sample, and the sample is a 10 mm×10 mm×55 mm Charpy U-shaped notch sample. Its wear resistance and impact toughness are shown in Table 1. After the silicon-manganese alloy steel is subjected to modification and quenching-partitioning heat treatment, due to the refinement of the martensite lath, dispersed fine carbides appear in the matrix, and there is also a certain amount of stable residual austenite, which improves the wear resistance and impact toughness of the silicon-manganese alloy steel to a certain extent. The present invention is expected to be used to prepare power connection hardware, overcome the problem of premature wear and failure of power connection hardware caused by strong winds carrying sand and dust, eliminate the hidden dangers of strong wind sand to the safe and stable operation of my country's power transmission lines, and the promotion and application of it will have good social benefits.

[0052] Table 1 Mechanical properties of modified silicon-manganese alloy steel

[0053] In order to further improve the wear resistance of silicon-manganese alloy steel and better play its cost-effective advantage, the present invention is based on silicon-manganese steel, through component optimization, heat treatment process improvement, to develop a new type of silicon-manganese low alloy cast steel. The purpose of the present invention is to provide a chemical composition of silicon-manganese alloy steel modified outside the furnace and a heat treatment method thereof, so as to improve the toughness and wear resistance of silicon-manganese alloy steel. Its main characteristics are that elements such as Cr and B are added to the silicon-manganese alloy steel, combined with rare earth magnesium alloy and Nb, V composite modification treatment, through the effect of fine grain strengthening, to improve its wear resistance, in addition, in the silicon-manganese alloy steel after the furnace modification, a new type of heat treatment process-quenching-partitioning heat treatment process is used, by increasing the residual austenite content and the precipitation strengthening of carbides to further improve the wear resistance and toughness of the alloy steel.

[0054] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.

[0055] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

Claims

1. A furnace-modified silicon-manganese alloy steel, characterized in that: Calculated by weight percentage: 0.5~0.55 wt.% C, 1.97~2.04 wt.% Mn, 1.5~1.6 wt.% Si, 0.98~1.02 wt.% Cr, 0.39~0.41 wt.% Mo, 0.004~0.007wt.% B, 0.08~0.12wt.% Mg, 0.35wt.% rare earth magnesium alloy, 0.04~0.07 wt.% Nb, 0.13~0.15wt.% Ce, 0.03~0.05 wt.% V, and the rest is Fe and inevitable trace impurities.

2. The out-of-furnace modified silicon-manganese alloy steel according to claim 1, characterized in that: The rare earth magnesium alloy includes, by mass percentage, 11.07-12.22 wt.% Mg, 2.01-2.56 wt.% rare earth elements, 40.38-42.25 wt.% Si, 2.05-2.60 wt.% Ca, and the remainder is Fe.

3. A heat treatment method for modified silicon-manganese alloy steel outside the furnace, characterized in that: The following steps are involved: According to the chemical composition of the out-of-furnace modified silicon-manganese alloy steel as described in any one of claims 1-2, scrap steel, ferrochrome, ferrosilicon, ferroboron and ferromanganese are smelted, and a deoxidizer is added after the molten steel is heated to a first temperature; The molten steel is transferred to a ladle, the bottom of which contains rare earth magnesium alloy, ferroniobium and ferrovanadium modifiers; After cooling the molten steel to a second temperature, casting is performed to obtain a sample; The samples were austenitized, quenched and then partitioned.

4. The heat treatment method for the out-of-furnace modified silicon-manganese alloy steel according to claim 3, characterized in that: The first temperature is 1640~1660°C.

5. The heat treatment method for out-of-furnace modified silicon-manganese alloy steel according to claim 3, characterized in that: The amount of deoxidizer added is 0.04-0.06% of the mass of the silicon-manganese alloy steel modified outside the furnace.

6. The heat treatment method for out-of-furnace modified silicon-manganese alloy steel according to claim 3, characterized in that: The second temperature is 1550-1570°C.

7. The heat treatment method for the out-of-furnace modified silicon-manganese alloy steel according to claim 3, characterized in that: The temperature of austenitizing treatment is 850-870℃, and the holding time is 30-35min.

8. The heat treatment method for out-of-furnace modified silicon-manganese alloy steel according to claim 3, characterized in that: The quenching temperature is 170-190℃ and the holding time is 120-140s.

9. The heat treatment method for out-of-furnace modified silicon-manganese alloy steel according to claim 3, characterized in that: The temperature of the distribution treatment is 340-360°C, and the holding time is 60-70s.

10. The heat treatment method for out-of-furnace modified silicon-manganese alloy steel according to claim 3, characterized in that: The microstructure of the heat-treated out-of-furnace modified silicon-manganese alloy steel includes: lath martensite with a width ranging from 200 to 300 nm, dispersed carbides and retained austenite with a volume percentage of 3-5%.

11. The heat treatment method for out-of-furnace modified silicon-manganese alloy steel according to claim 3, characterized in that: The hardness of the furnace-modified silicon-manganese alloy steel after heat treatment is above 58HRC, and the wear resistance is 10~11 min / mg.